Iatrogenic emboli during mechanical thrombectomy for acute ischemic stroke: comparison between stent retriever technique and contact aspiration-a retrospective case-control study - Mouyal, Samuel J; Granger, Benjamin; Janot, Kevin; Ifergan, Héloïse; Hoche, Clémence; Herbreteau, Denis; Bibi, Richard Edwige; Boulouis, Grégoire; Bala, Fouzi; Donnard, Baptiste; Barrot, Valère; Giubbolini, Francesca; et al. (Journal of neurointerventional surgery, 2025)
Mechanical thrombectomy (MT) is an effective treatment for acute ischemic stroke from large vessel occlusion (LVO). While embolization to a new territory (ENT) after MT is well-documented, data on embolization in the same distal territory (EDT) are limited. Achieving modified Treatment In Cerebral Infarction (mTICI) 3 reperfusion presents significant clinical benefits over mTICI 2b/2c, necessitating strategies to reduce both ENT and EDT. Previous studies suggest higher rates of EDTs with contact aspiration compared with stentrievers. However, comprehensive comparison studies in clinical practice are scarce. This study compares the rates of overall clot emboli (OCE) between these MT strategies. A retrospective, multicenter observational study was conducted at four university hospitals in France from January 2015 to November 2019. Adult patients (≥18 years) with acute ischemic stroke due to LVO, treated with either contact aspiration (ADAPT, A Direct Aspiration First Pass Technique) or stentrievers, specifically using the Embotrap device to maintain sample homogeneity, were included. Digital subtraction angiography was used for imaging, with two independent, blinded reviewers assessing OCE post-first MT pass. Propensity score full matching and independent sample testing were employed to evaluate OCE after the first MT pass. A significant difference in OCE rates was observed between contact aspiration and stentriever techniques, with the stentriever technique resulting in fewer embolic events compared with ADAPT, based on a propensity score analysis that accounts for key confounding factors. A statistically significant reduction in embolic events was observed with the stentriever technique compared with contact aspiration. These results suggest that the stentriever method may offer a safer profile in terms of embolic risk for LVO interventions, and should be considered over contact aspiration when embolic risk is a primary concern, while also considering individual patient factors.